Macrophage activation marker, soluble CD163, is an independent predictor of short‐term mortality in patients with cirrhosis and bacterial infection. (5th May 2016) - Tornai, Tamas; Vitalis, Zsuzsanna; Sipeki, Nora; Dinya, Tamas; Tornai, David; Antal‐Szalmas, Peter; Karanyi, Zsolt; Tornai, Istvan; Papp, Maria
Abstract: Background & Aims: Innate immune system dysfunction is common in advanced cirrhosis, with a central role of the monocyte/macrophage system. Monocytes and macrophages express the scavenger receptor CD163, which is regulated by inflammatory mediators. Cleavage of the receptor leads to the formation of soluble (s)CD163 that represents an anti‐inflammatory response. We aimed to study the clinical importance of sCD163 in cirrhosis. Methods: Sera of 378 patients were assayed for sCD163 by ELISA [193 outpatients and 185 patients with acute decompensation (AD)]. A 5‐year follow‐up observational study was conducted to assess the possible association between sCD163 level and poor disease outcomes. Results: sCD163 level was associated with disease severity, but not with the presence of varices or prior variceal bleeding. In outpatients, sCD163 level did not predict the development of disease‐specific complications or the long‐term mortality. In patients with AD episode, sCD163 level was significantly higher compared to outpatients but only in the presence of bacterial infection (INF) (AD‐INF:4586, AD‐NON‐INF:3792 and outpatients: 3538 ng/ml, P < 0.015 and P = 0.001, respectively). sCD163 level gradually increased according to severity of infection. During bacterial infections, high sCD163 level (>7000 ng/ml) was associated with increased mortality rate (42% vs. 17%, P < 0.001) and was identified as an independent predictor of 28‐day mortality (hazard ratio:2.96, 95% confidence intervals:1.27–6.95) in multivariate Cox‐regression model comprising aetiology, co‐morbidity, model for end‐stage liver disease score and leucocyte count as covariates. Conclusions: High sCD163 level is useful to identify patients with high‐risk of death during an AD episode complicated by bacterial infection. This finding serves as an additional hint towards the significance of anti‐inflammatory response during bacterial infection.